The Shakespeare Book - Editor Fox, Satu (London DK Publishing, 2015)
Whether you are new to the poetry and proses of Shakespeare, and in need of a guide through the complex plots and unfamiliar language, or looking for a fresh perspective on his much-loved plays and sonnets, this book will shed light on the work of one of world literature's greatest figures"
Include Illustration and Index
Keywords: Characters and characteristics -- Shakespeare, William, 1564-1616